The double sword dance. - Grant, Horatio N. (Buffalo, N.Y., 1895)
Part of a series of pamphlets published by Grant, this work provides preparatory exercises and instructions for steps including the pas de basque, waltz turn, and shuffle. Grant notes that the double sword dance can be performed as a solo or duet.
Caption title.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Sword-dance -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals; Theatrical Dance